Ceramsite composite proppant and preparation method thereof
By using ceramsite composite proppant and using the temperature triggering effect of Fe3O4 nanoparticles to form a three-dimensional network structure, it solves the problem of lack of temperature responsiveness of traditional hydraulic fracturing technology, optimizes the support effect and flow conductivity, and adapts to complex formation conditions. , and improve the development efficiency and economic benefits of oil and gas reservoirs.
Patent Information
- Application Number
- CN202411422429.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional hydraulic fracturing technology lacks temperature responsiveness, resulting in unstable support effect, difficulty in optimizing fracturing fluid performance, inability to cope with dynamic changes in formation temperature, limited application under special geological conditions, and increased environmental risks.
The use of ceramics composite support agents, which consists of alumina, oxide, magnesium oxide, silicon oxide, silicon dioxide, Fe3O4 nanometer particles, T IO2 nanoparticles, medium silicon dioxide, and degradable polymer. Formation to form a stable three -dimensional network structure to improve support and diversion capabilities.
The support effect and diversion capabilities are optimized in different temperature environments, adapting to complex strata conditions, extending the duration of fracture effects, improving the development efficiency and economic benefits of oil and gas, and good environmental compatibility.
Smart Images

Figure BDA0005081200450000131 
Figure BDA0005081200450000151 
Figure BDA0005081200450000161
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oil extraction, and in particular to a ceramsite composite proppant and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand and the gradual depletion of conventional oil and gas resources, the development of unconventional oil and gas resources has become an important direction of the petroleum industry. As a key means to increase the production of unconventional oil and gas, hydraulic fracturing technology has been widely used in the past few decades. However, traditional hydraulic fracturing technology still has many shortcomings when facing complex formation conditions. One of the most prominent problems is the lack of temperature responsiveness, which seriously limits the fracturing effect and the increase in oil and gas production.
[0003] Traditional hydraulic fracturing technology mainly relies on injecting high-pressure liquid into the formation to form cracks, and uses proppants (such as quartz sand, expanded clay, etc.) to keep the cracks open. However, the biggest limitation of this method is that it cannot make corresponding adjustments according to changes in formation temperature. Underground temperature increases with depth, and temperature conditions in different oil and gas reservoirs vary significantly. Even different areas of the same oil and gas reservoir may have temperature gradients. Traditional proppants cannot respond to these temperature changes, leading to a series of problems.
[0004] First, the lack of temperature responsiveness makes it difficult to optimize the performance of proppants in different temperature environments. In low-temperature areas, proppants may be too hard to effectively fill irregular cracks, resulting in uneven support; while in high-temperature areas, some proppants may soften or deform and lose their original support capacity. This "one-size-fits-all" support method cannot adapt to the complex and changeable formation temperature environment, which seriously affects the consistency and predictability of the fracturing effect.
[0005] Secondly, the lack of temperature responsiveness leads to unstable performance of fracturing fluid. The viscosity and rheological properties of traditional fracturing fluids often change significantly with temperature. In high temperature environments, fracturing fluids may degrade prematurely and lose their ability to carry sand and suspend proppants, resulting in proppant sedimentation and bridging, forming areas of low conductivity. Conversely, in low temperature areas, fracturing fluids may maintain too high a viscosity, affecting the effective placement of proppants. This temperature dependence seriously affects the effectiveness and controllability of fracturing operations.
[0006] More importantly, the lack of temperature responsiveness makes traditional technologies unable to cope with dynamic changes in formation temperature. During oil and gas production, water injection, gas injection and other operations will cause changes in formation temperature. Traditional proppants and fracturing fluids cannot make real-time adjustments to these temperature changes, which may cause the originally effective propping to gradually fail, or the originally suitable fluid properties to become no longer applicable. This lag seriously affects the long-term development benefits of oil and gas reservoirs.
[0007] In addition, the lack of temperature responsiveness also limits the application of fracturing technology in special geological conditions. For example, in areas with abnormal geothermal gradients or temperature-sensitive reservoirs, traditional technology is difficult to accurately control the fracturing process, which may cause unexpected formation reactions or damage the reservoir.
[0008] Environmental issues are also closely related to the lack of temperature responsiveness. Since the performance of proppants and fracturing fluids cannot be optimized according to temperature changes, traditional technologies often require the use of more chemical additives to cope with various possible temperature conditions, which not only increases costs but also increases environmental risks.
[0009] In summary, the lack of temperature responsiveness, a key feature of conventional hydraulic fracturing technology, has led to many problems, including unstable support effects, difficulty in optimizing fracturing fluid performance, inability to cope with dynamic changes in formation temperature, limited application under special geological conditions, and increased environmental risks. These defects have seriously restricted the development efficiency and economic benefits of unconventional oil and gas reservoirs. Summary of the invention
[0010] In order to solve or partially solve the problems existing in the related art, the present invention provides a ceramsite composite proppant and a preparation method thereof.
[0011] The present invention provides a first aspect of a ceramsite composite proppant and a preparation method thereof, comprising the following steps:
[0012] S1. 60-80kg alumina powder, 15-25kg zirconium oxide powder, 3-7kg magnesium oxide powder, 3-7kg silica powder, 0.3-0.7kg dispersant and 45-60L deionized water were added to a ball mill and milled for 6-10 hours;
[0013] S2. The ball-milled slurry is pumped into a spray drying tower with an inlet temperature of 230-270°C and an outlet temperature of 100-120°C, and the dried particles are collected;
[0014] S3. The dried particles are filled into a special dodecahedron mold and cold isostatically pressed at a pressure of 250-350 MPa;
[0015] S4. Place the formed particles into a high temperature furnace, heat to 1550-1650°C at a rate of 2-4°C / min, keep warm for 3-5 hours, and then cool naturally to room temperature;
[0016] S5. Use a standard sieve to select particles in the range of 0.5-0.9 mm as the main support unit;
[0017] S6. Dissolve 10-14 kg N-isopropylacrylamide (NIPAM), 2-2.5 kg acrylamide (AM), and 0.6-0.9 kg N, N'-methylenebisacrylamide in 45-55 L deionized water, add 0.08-0.12 kg initiator, and react at 60-70 ° C for 3-5 hours under nitrogen protection;
[0018] S7. cooling the reaction product, chopping it, and freeze-drying it to obtain hydrogel particles;
[0019] S8. 3.5-4.5 kg of polylactic acid (PLA) and 0.4-0.5 kg of polyethylene glycol (PEG) were dissolved in 35-45 L of dichloromethane to form a solution;
[0020] S9. Using coaxial spray drying technology, the inner layer is sprayed with hydrogel particles and an appropriate amount of aqueous suspension, and the outer layer is sprayed with PLA / PEG solution. The drying temperature is 35-45°C, and microcapsules in the range of 0.15-0.35 mm are collected and screened as connecting units;
[0021] S10. Mix 2.5-3.5kgFe3O4 nanoparticles, 1.2-1.8kgT i O2 nanoparticles and 0.4-0.6kg mesoporous silica, and add 4-6L anhydrous ethanol;
[0022] S11. The mixture was uniformly dispersed in ethanol using ultrasonic dispersion technology for 25-35 minutes, and then spray-dried at an inlet temperature of 170-190°C and an outlet temperature of 75-85°C to obtain a composite trigger powder;
[0023] S12 according to the weight ratio of 75-85: 12-18: 3-7 mixed body support unit, connecting unit and smart trigger agent, using a V-type mixer fully mixed for 25-35 minutes;
[0024] S13. The final mixed product is packaged and vacuum packed, with each bag weighing 20-30 kg.
[0025] Furthermore, it is characterized in that the purity of the aluminum oxide powder is ≥99.9%, and the particle size is <1μm; the purity of the zirconium oxide powder is ≥99.5%, and the particle size is <1μm; the purity of the magnesium oxide powder is ≥99%, and the particle size is <1μm; the purity of the silicon dioxide powder is ≥99.5%, and the particle size is <1μm.
[0026] Furthermore, it is characterized in that the dispersant is ammonium polyacrylate.
[0027] Furthermore, it is characterized in that the initiator in step 6 is ammonium persulfate.
[0028] Furthermore, it is characterized in that the molecular weight of the polyethylene glycol used in step 9 is 5000-7000.
[0029] Furthermore, in step 10, the average particle size of the Fe3O4 nanoparticles is 30-70 nm, the average particle size of the TiO2 nanoparticles is 20-30 nm, and the average pore size of the mesoporous silica is 4-6 nm.
[0030] Furthermore, in step 12, the weight ratio of the main support unit, the connection unit and the intelligent triggering agent is 80:15:5.
[0031] The second aspect of the present application provides a ceramsite composite proppant, which is prepared according to the above-mentioned preparation method.
[0032] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present invention.
[0033] Beneficial technical effects of the present invention:
[0034] The Fe3O4 nano-trigger in the components of the present invention can be accurately activated within the range of 70-80°C, and the trigger temperature can be fine-tuned by adjusting the particle size (30-50nm) to adapt to reservoirs of different depths. The formed network structure has a compressive strength that is about 30% higher than that of traditional 20 / 40 mesh quartz sand, and can withstand a closure pressure of up to 80MPa. At the same time, it creates a connected porosity of 40-45%, which increases the long-term flow conductivity by 50-60% compared with conventional proppant stacking. Under high-speed fluid scouring at 15m / s, the proppant loss rate is less than 5%, which is much better than traditional proppant. NIPAM-AM hydrogel can adjust the expansion degree (100%-1000%) according to the size of the surrounding voids, and adapt to the crack width range of 0.1-2mm. The system is mainly composed of inorganic ceramics and degradable polymers, has good environmental compatibility, and PLA can be completely degraded within 6-12 months. The formed network structure is stable for more than 24 months under simulated formation conditions (80℃, 50MPa), which is 2-3 times longer than the traditional hydraulic fracturing effect. By adjusting the Fe3O4 / TiO2 ratio (6:3 to 7:2) and the NIPAM:AM ratio (4:1 to 5:1), the trigger temperature (±2℃) and the degree of expansion (±10%) can be precisely controlled. The system is suitable for unconventional oil and gas reservoirs such as conventional sandstone, carbonate rock and shale, and can still work effectively under high temperature and high pressure conditions of 120℃ and 100MPa. TiO2's sensitivity to specific wavelengths (such as 365nm ultraviolet light) provides the possibility of remotely controlling reservoir performance through optical fiber systems in the future. Although the initial cost is 30-40% higher than conventional 20 / 40 mesh quartz sand, due to the increase in production capacity (average 50%) and the extension of service life (2-3 times), the return on investment can be achieved within 3-5 years, and the long-term economic benefits are significant. DETAILED DESCRIPTION
[0035] The optional embodiments of the present invention will be described in more detail below. Although the optional embodiments of the present invention are described, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0036] The terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0037] The present invention provides a ceramsite composite proppant and a preparation method thereof, comprising the following steps:
[0038] S1. 60-80kg alumina powder, 15-25kg zirconium oxide powder, 3-7kg magnesium oxide powder, 3-7kg silica powder, 0.3-0.7kg dispersant and 45-60L deionized water were added to a ball mill and milled for 6-10 hours;
[0039] S2. The ball-milled slurry is pumped into a spray drying tower with an inlet temperature of 230-270°C and an outlet temperature of 100-120°C, and the dried particles are collected;
[0040] S3. The dried particles are filled into a special dodecahedron mold and cold isostatically pressed at a pressure of 250-350 MPa;
[0041] S4. Place the formed particles into a high temperature furnace, heat to 1550-1650°C at a rate of 2-4°C / min, keep warm for 3-5 hours, and then cool naturally to room temperature;
[0042] S5. Use a standard sieve to select particles in the range of 0.5-0.9 mm as the main support unit;
[0043] S6. Dissolve 10-14 kg N-isopropylacrylamide (NIPAM), 2-2.5 kg acrylamide (AM), and 0.6-0.9 kg N, N'-methylenebisacrylamide in 45-55 L deionized water, add 0.08-0.12 kg initiator, and react at 60-70 ° C for 3-5 hours under nitrogen protection;
[0044] S7. cooling the reaction product, chopping it, and freeze-drying it to obtain hydrogel particles;
[0045] S8. 3.5-4.5 kg of polylactic acid (PLA) and 0.4-0.5 kg of polyethylene glycol (PEG) were dissolved in 35-45 L of dichloromethane to form a solution;
[0046] S9. Using coaxial spray drying technology, the inner layer is sprayed with hydrogel particles and an appropriate amount of aqueous suspension, and the outer layer is sprayed with PLA / PEG solution. The drying temperature is 35-45°C, and microcapsules in the range of 0.15-0.35 mm are collected and screened as connecting units;
[0047] S10. Mix 2.5-3.5kgFe3O4 nanoparticles, 1.2-1.8kgT i O2 nanoparticles and 0.4-0.6kg mesoporous silica, and add 4-6L anhydrous ethanol;
[0048] S11. The mixture was uniformly dispersed in ethanol using ultrasonic dispersion technology for 25-35 minutes, and then spray-dried at an inlet temperature of 170-190°C and an outlet temperature of 75-85°C to obtain a composite trigger powder;
[0049] S12 according to the weight ratio of 75-85: 12-18: 3-7 mixed body support unit, connecting unit and smart trigger agent, using a V-type mixer fully mixed for 25-35 minutes;
[0050] S13. The final mixed product is packaged and vacuum packed, with each bag weighing 20-30 kg.
[0051] The working principle of the product of the present invention involves a complex process in multiple stages. First, a mixture consisting of ceramic microspheres (main support units), microcapsules encapsulating hydrogels (connection units) and nanocomposite triggers is injected into the formation fractures along with the fracturing fluid. When the system enters the formation, the Fe3O4 nanoparticles begin to sense the downhole temperature. Once the temperature reaches a preset threshold (usually 70-80°C), the Fe3O4 nanoparticles catalyze the hydrolysis and degradation of the PLA shell. As the PLA gradually decomposes, the internal NIPAM-AM copolymer hydrogel is exposed to the formation environment. Since the temperature at this time is higher than the phase transition temperature of the hydrogel (about 32°C), the hydrogel molecular chains change from hydrophobic to hydrophilic and begin to absorb water and swell rapidly. The expanded hydrogel fills the gaps between adjacent ceramic microspheres and connects them through physical entanglement and chemical bonding. At the same time, the TiO2 nanoparticles promote the cross-linking of the hydrogel at high temperatures, further enhancing the stability of the network structure. As more and more connection units are activated, the entire system gradually forms an interconnected three-dimensional network structure. This network not only provides continuous support to prevent the formation from closing, but also creates excellent diversion channels. Mesoporous silica acts as a slow-release agent in this process, regulating the rate of the entire reaction. The formed network structure can adapt to the irregular shape of the formation and fill cracks and pores of various sizes, thereby maximizing the support effect and diversion capacity. Over time, PLA completely degrades, while the hydrogel network exists for a long time and continues to play a supporting and diversion role. The entire process is automatic without additional intervention, and can adapt to oil and gas reservoirs of different depths and geological conditions to achieve intelligent fracturing support.
[0052] In one embodiment of the present invention, it is characterized in that the purity of the aluminum oxide powder is ≥99.9%, and the particle size is <1μm; the purity of the zirconium oxide powder is ≥99.5%, and the particle size is <1μm; the purity of the magnesium oxide powder is ≥99%, and the particle size is <1μm; the purity of the silicon dioxide powder is ≥99.5%, and the particle size is <1μm.
[0053] In one embodiment of the present invention, it is characterized in that the dispersant is ammonium polyacrylate.
[0054] In one embodiment of the present invention, it is characterized in that the initiator in step 6 is ammonium persulfate.
[0055] In one embodiment of the present invention, it is characterized in that the molecular weight of the polyethylene glycol used in step 9 is 5000-7000.
[0056] In one embodiment of the present invention, in step 10, the average particle size of the Fe3O4 nanoparticles is 30-70 nm, the average particle size of the TiO2 nanoparticles is 20-30 nm, and the average pore size of the mesoporous silica is 4-6 nm.
[0057] In one embodiment of the present invention, in step 12, the weight ratio of the main body support unit, the connection unit and the smart trigger is 80:15:5.
[0058] In one embodiment of the present invention, a ceramsite composite proppant is provided, which is prepared according to the above-mentioned preparation method.
[0059] For the purpose of greater clarity, the invention is described in detail through the following examples.
[0060] Example 1
[0061] Embodiment 1:
[0062] The preparation method of the ceramsite composite proppant of this embodiment is as follows:
[0063] S1. 60 kg of alumina powder (purity ≥ 99.9%, particle size < 1 μm), 15 kg of zirconium oxide powder (purity ≥ 99.5%, particle size < 1 μm), 3 kg of magnesium oxide powder (purity ≥ 99%, particle size < 1 μm), 3 kg of silicon dioxide powder (purity ≥ 99.5%, particle size < 1 μm), 0.3 kg of ammonium polyacrylate dispersant and 45 L of deionized water were added to a ball mill and milled for 6 hours;
[0064] S2. The ball-milled slurry is pumped into a spray drying tower with an inlet temperature of 230°C and an outlet temperature of 100°C, and the dried particles are collected;
[0065] S3. The dried particles are filled into a special dodecahedron mold and cold isostatically pressed at a pressure of 250 MPa;
[0066] S4. The formed particles are placed in a high temperature furnace, heated to 1550°C at a rate of 2°C / min, kept at this temperature for 3 hours, and then cooled naturally to room temperature;
[0067] S5. Use a standard sieve to select particles in the range of 0.5-0.9 mm as the main support unit;
[0068] S6. 10 kg N-isopropyl acrylamide (NIPAM), 2 kg acrylamide (AM), and 0.6 kg N, N'-methylenebisacrylamide were dissolved in 45 L of deionized water, 0.08 kg of ammonium persulfate initiator was added, and the reaction was carried out at 60 ° C for 3 hours under nitrogen protection;
[0069] S7. cooling the reaction product, chopping it, and freeze-drying it to obtain hydrogel particles;
[0070] S8. 3.5 kg of polylactic acid (PLA) and 0.4 kg of polyethylene glycol (PEG, molecular weight 5000) were dissolved in 35 L of dichloromethane to form a solution;
[0071] S9. Using coaxial spray drying technology, the inner layer was sprayed with hydrogel particles and an appropriate amount of aqueous suspension, and the outer layer was sprayed with PLA / PEG solution. The drying temperature was 35°C, and microcapsules in the range of 0.15-0.35 mm were collected and screened as connecting units;
[0072] S10. 2.5 kg Fe3O4 nanoparticles (average particle size 30 nm), 1.2 kg TiO2 nanoparticles (average particle size 20 nm) and 0.4 kg commercial mesoporous silica (average pore size 4 nm) were mixed and 4 L of anhydrous ethanol was added;
[0073] S11. The mixture was uniformly dispersed in ethanol using ultrasonic dispersion technology for 25 minutes, and then spray-dried at an inlet temperature of 170°C and an outlet temperature of 75°C to obtain a composite trigger powder;
[0074] S12. The main support unit, the connecting unit and the smart triggering agent were mixed in a weight ratio of 75:12:3 and mixed thoroughly for 25 minutes using a V-type mixer;
[0075] S13. The final mixed product is packaged and vacuum packed, with each bag weighing 20 kg.
[0076] Embodiment 2:
[0077] The preparation method of the ceramsite composite proppant of this embodiment is as follows:
[0078] S1. 70 kg of alumina powder (purity ≥ 99.9%, particle size < 1 μm), 20 kg of zirconium oxide powder (purity ≥ 99.5%, particle size < 1 μm), 5 kg of magnesium oxide powder (purity ≥ 99%, particle size < 1 μm), 5 kg of silicon dioxide powder (purity ≥ 99.5%, particle size < 1 μm), 0.5 kg of ammonium polyacrylate dispersant and 52.5 L of deionized water were added to a ball mill and milled for 8 hours;
[0079] S2. The ball-milled slurry is pumped into a spray drying tower with an inlet temperature of 250°C and an outlet temperature of 110°C, and the dried particles are collected;
[0080] S3. The dried particles are filled into a special dodecahedron mold and cold isostatically pressed at a pressure of 300 MPa;
[0081] S4. The formed particles are placed in a high temperature furnace, heated to 1600°C at a rate of 3°C / min, kept at this temperature for 4 hours, and then cooled naturally to room temperature;
[0082] S5. Use a standard sieve to select particles in the range of 0.5-0.9 mm as the main support unit;
[0083] S6. 12 kg N-isopropyl acrylamide (NIPAM), 2.25 kg acrylamide (AM), and 0.75 kg N, N'-methylenebisacrylamide were dissolved in 50 L deionized water, 0.1 kg ammonium persulfate initiator was added, and the reaction was carried out at 65 ° C for 4 hours under nitrogen protection;
[0084] S7. cooling the reaction product, chopping it, and freeze-drying it to obtain hydrogel particles;
[0085] S8. 4 kg of polylactic acid (PLA) and 0.45 kg of polyethylene glycol (PEG, molecular weight 6000) were dissolved in 40 L of dichloromethane to form a solution;
[0086] S9. Using coaxial spray drying technology, the inner layer was sprayed with hydrogel particles and an appropriate amount of aqueous suspension, and the outer layer was sprayed with PLA / PEG solution. The drying temperature was 40°C, and microcapsules in the range of 0.15-0.35 mm were collected and screened as connecting units;
[0087] S10. 3 kg Fe3O4 nanoparticles (average particle size 50 nm), 1.5 kg TiO2 nanoparticles (average particle size 25 nm) and 0.5 kg commercial mesoporous silica (average pore size 5 nm) were mixed and 5 L of anhydrous ethanol was added;
[0088] S11. The mixture was uniformly dispersed in ethanol using ultrasonic dispersion technology for 30 minutes, and then spray-dried at an inlet temperature of 180°C and an outlet temperature of 80°C to obtain a composite trigger powder;
[0089] S12. The main support unit, the connecting unit and the smart trigger were mixed in a weight ratio of 80:15:5 and mixed thoroughly for 30 minutes using a V-type mixer;
[0090] S13. The final mixed product is packaged and vacuum packed, with each bag weighing 25 kg.
[0091] Embodiment 3:
[0092] The preparation method of the ceramsite composite proppant of this embodiment is as follows:
[0093] S1. 80 kg of alumina powder (purity ≥ 99.9%, particle size < 1 μm), 25 kg of zirconium oxide powder (purity ≥ 99.5%, particle size < 1 μm), 7 kg of magnesium oxide powder (purity ≥ 99%, particle size < 1 μm), 7 kg of silicon dioxide powder (purity ≥ 99.5%, particle size < 1 μm), 0.7 kg of ammonium polyacrylate dispersant and 60 L of deionized water were added to a ball mill and milled for 10 hours;
[0094] S2. The ball-milled slurry is pumped into a spray drying tower with an inlet temperature of 270°C and an outlet temperature of 120°C, and the dried particles are collected;
[0095] S3. The dried particles are filled into a special dodecahedron mold and cold isostatically pressed at a pressure of 350 MPa;
[0096] S4. The formed particles are placed in a high temperature furnace, heated to 1650°C at a rate of 4°C / min, kept at this temperature for 5 hours, and then cooled naturally to room temperature;
[0097] S5. Use a standard sieve to select particles in the range of 0.5-0.9 mm as the main support unit;
[0098] S6. 14 kg N-isopropyl acrylamide (NIPAM), 2.5 kg acrylamide (AM), and 0.9 kg N, N'-methylenebisacrylamide were dissolved in 55 L deionized water, 0.12 kg ammonium persulfate initiator was added, and the reaction was carried out at 70 ° C under nitrogen protection for 5 hours;
[0099] S7. cooling the reaction product, chopping it, and freeze-drying it to obtain hydrogel particles;
[0100] S8. 4.5 kg of polylactic acid (PLA) and 0.5 kg of polyethylene glycol (PEG, molecular weight 7000) were dissolved in 45 L of dichloromethane to form a solution;
[0101] S9. Using coaxial spray drying technology, the inner layer was sprayed with hydrogel particles and an appropriate amount of aqueous suspension, and the outer layer was sprayed with PLA / PEG solution. The drying temperature was 45°C, and microcapsules in the range of 0.15-0.35 mm were collected and screened as connecting units;
[0102] S10. 3.5 kg Fe3O4 nanoparticles (average particle size 70 nm), 1.8 kg TiO2 nanoparticles (average particle size 30 nm) and 0.6 kg commercial mesoporous silica (average pore size 6 nm) were mixed and 6 L of anhydrous ethanol was added;
[0103] S11. The mixture was uniformly dispersed in ethanol using ultrasonic dispersion technology for 35 minutes, and then spray-dried at an inlet temperature of 190°C and an outlet temperature of 85°C to obtain a composite trigger powder;
[0104] S12. The main support unit, the connecting unit and the smart trigger were mixed in a weight ratio of 85:18:7 and mixed thoroughly for 35 minutes using a V-type mixer;
[0105] S13. The final mixed product is packaged and vacuum packed, with each bag weighing 30 kg.
[0106] Test Example 1 Temperature Responsiveness Test
[0107] Purpose: To verify the temperature triggering accuracy and response characteristics of the product
[0108] Materials and equipment:
[0109] Example 2 Sample Preparation
[0110] Constant temperature water bath (accuracy ±0.1℃)
[0111] Scanning electron microscope (SEM, model: JEOL JSM-7800F )
[0112] Optical microscope (Model: Ollympus BX53 )
[0113] Electronic balance (accuracy 0.0001g)
[0114] Oven
[0115] Sample bottles
[0116] Experimental steps:
[0117] Prepare 5 groups of samples of equal weight (2 g each) and label them as A, B, C, D, and E.
[0118] The constant temperature water bath was set to 60°C, 70°C, 75°C, 80°C and 90°C respectively.
[0119] Samples AE were placed in water baths of corresponding temperatures respectively.
[0120] Take a small amount of sample at 0, 10, 20, 30, 60, and 120 minutes and quickly cool to room temperature.
[0121] The weight change of the sample was measured using an electronic balance.
[0122] Use an optical microscope to observe the macroscopic changes of the samples.
[0123] The 60-min sample was freeze-dried and the microstructure was observed using SEM.
[0124] Experimental results:
[0125] Weight change percentage (%):
[0126]
[0127] Optical microscope observation results:
[0128] 60℃: After 120 minutes, the sample has almost no change in appearance.
[0129] 70°C: Obvious particle expansion began to be observed after 30 minutes, and about 50% of the particles showed obvious expansion after 120 minutes.
[0130] 75°C and 80°C: Significant expansion can be observed after 20 minutes, and most of the particles are fully expanded after 60 minutes.
[0131] 90°C: Rapid expansion can be observed after 10 minutes, and almost all particles are fully expanded after 30 minutes.
[0132] in conclusion:
[0133] The product exhibits optimal temperature responsiveness in the range of 70-80°C, which is consistent with the design goal.
[0134] Under the conditions of 75℃ and 80℃, the system reaches the ideal expansion state within 60 minutes and forms a stable network structure.
[0135] The experimental results demonstrate that the intelligent self-assembled support network system has excellent temperature-triggered accuracy and controllable response characteristics.
[0136] Test Example 2: Support force test
[0137] Purpose: To compare the supporting capacity and flow conductivity of the product in Example 2 with that of conventional 20 / 40 mesh quartz sand. Materials and equipment:
[0138] Example 2 Product
[0139] 20 / 40 mesh quartz sand (control group)
[0140] API standard pressure chamber (Model: HAIAN HHS-1000)
[0141] High temperature and high pressure flow tester (Model: TEMCO FCS-1000)
[0142] Pressure sensor (accuracy ±0.1MPa)
[0143] Flow meter (accuracy ±0.1mL / min)
[0144] Constant temperature box (temperature range: 25-150℃, accuracy ±0.5℃)
[0145] Experimental steps:
[0146] The intelligent self-assembly support network system and 20 / 40 mesh quartz sand samples were prepared separately, 100 g each.
[0147] The samples were loaded into the API standard pressure chamber with an initial filling thickness of 10 mm.
[0148] The thermostat temperatures were set to 25°C, 50°C, 75°C and 100°C respectively.
[0149] Under each temperature condition, the pressure was gradually increased and the conductivity was tested at 10MPa, 30MPa, 50MPa, 70MPa and 90MPa respectively.
[0150] The conductivity under different pressures was measured using a high temperature and high pressure conductivity tester, and each pressure point was maintained for 2 hours to reach a stable state.
[0151] The conductivity data were recorded for each temperature and pressure condition.
[0152] Experimental results:
[0153] Conductivity data (unit: D·cm, 1D·cm=9.869233×10^-13m 3 )
[0154]
[0155] Conductivity retention rate (based on the conductivity at 10MPa):
[0156]
[0157] Support strength improvement percentage (compared with 20 / 40 mesh quartz sand):
[0158]
[0159] in conclusion:
[0160] The product of Example 2 showed better conductivity than 20 / 40 mesh quartz sand under all test conditions.
[0161] As the temperature and pressure increase, the advantages of the product of Example 2 become more obvious. Under the conditions of 100°C and 90 MPa, its flow conductivity is 36.6% higher than that of 20 / 40 mesh quartz sand.
[0162] The product of Example 2 exhibits better high temperature adaptability. At 100°C, its conductivity retention rate is 74.6%, while that of 20 / 40 mesh quartz sand is only 60.4%.
[0163] Under high temperature and high pressure conditions (100° C., 90 MPa), the supporting force of the product of Example 2 is increased by 36.6% compared with the traditional 20 / 40 mesh quartz sand, exceeding the expected 30% increase.
[0164] The experimental results demonstrate that the product of Example 2 has significant advantages in supporting force and flow conductivity, especially under high temperature and high pressure conditions.
[0165] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made based on the present invention. Therefore, these modifications and improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a ceramsite composite proppant, characterized in that: The following steps are involved: S1. 60-80kg alumina powder, 15-25kg zirconium oxide powder, 3-7kg magnesium oxide powder, 3-7kg silica powder, 0.3-0.7kg dispersant and 45-60L deionized water were added to a ball mill and milled for 6-10 hours; S2. The ball-milled slurry is pumped into a spray drying tower with an inlet temperature of 230-270°C and an outlet temperature of 100-120°C, and the dried particles are collected; S3. The dried particles are filled into a special dodecahedron mold and cold isostatically pressed at a pressure of 250-350 MPa; S4. Place the formed particles into a high temperature furnace, heat to 1550-1650°C at a rate of 2-4°C / min, keep warm for 3-5 hours, and then cool naturally to room temperature; S5. Use a standard sieve to select particles in the range of 0.5-0.9 mm as the main support unit; S6. Dissolve 10-14 kg N-isopropylacrylamide (NIPAM), 2-2.5 kg acrylamide (AM), and 0.6-0.9 kg N, N'-methylenebisacrylamide in 45-55 L deionized water, add 0.08-0.12 kg initiator, and react at 60-70 ° C for 3-5 hours under nitrogen protection; S7. cooling the reaction product, chopping it, and freeze-drying it to obtain hydrogel particles; S8. 3.5-4.5 kg of polylactic acid (PLA) and 0.4-0.5 kg of polyethylene glycol (PEG) were dissolved in 35-45 L of dichloromethane to form a solution; S9. Using coaxial spray drying technology, the inner layer is sprayed with hydrogel particles and an appropriate amount of aqueous suspension, and the outer layer is sprayed with PLA / PEG solution. The drying temperature is 35-45°C, and microcapsules in the range of 0.15-0.35 mm are collected and screened as connecting units; S10. Mix 2.5-3.5 kg Fe3O4 nanoparticles, 1.2-1.8 kg TiO2 nanoparticles and 0.4-0.6 kg commercial mesoporous silica, and add 4-6 L anhydrous ethanol; S11. The mixture was uniformly dispersed in ethanol using ultrasonic dispersion technology for 25-35 minutes, and then spray-dried at an inlet temperature of 170-190°C and an outlet temperature of 75-85°C to obtain a composite trigger powder; S12 according to the weight ratio of 75-85: 12-18: 3-7 mixed body support unit, connecting unit and smart trigger agent, using a V-type mixer to mix for 25-35 minutes; S13. The final mixed product is packaged and vacuum packed, with each bag weighing 20-30 kg.
2. The preparation method according to claim 1, characterized in that The purity of the aluminum oxide powder is ≥99.9%, and the particle size is <1 μm; the purity of the zirconium oxide powder is ≥99.5%, and the particle size is <1 μm; the purity of the magnesium oxide powder is ≥99%, and the particle size is <1 μm; the purity of the silicon dioxide powder is ≥99.5%, and the particle size is <1 μm.
3. The preparation method according to claim 1, characterized in that: The dispersant is ammonium polyacrylate.
4. The preparation method according to claim 1, characterized in that: The initiator in step 6 is ammonium persulfate.
5. The preparation method according to claim 1, characterized in that: The molecular weight of the polyethylene glycol used in step 9 is 5000-7000.
6. The preparation method according to claim 1, characterized in that: In step 10, the average particle size of the Fe3O4 nanoparticles is 30-70 nm, the average particle size of the TiO2 nanoparticles is 20-30 nm, and the average pore size of the mesoporous silica is 4-6 nm.
7. The preparation method according to claim 1, characterized in that: In step 12, the weight ratio of the main support unit, the connection unit and the intelligent triggering agent is 80:15:
5.
8. A ceramsite composite proppant, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Degradable polymer core-shell microsphere loaded with protein drugs
CN106511315A
Preparation method of medium-density ultrahigh-strength ceramsite proppant
CN111960807A
Cited By
Petroleum fracturing propping agent containing fly ash component and preparation method thereof
CN120399671A